Advances in manufacturing, production management and process control : proceedings of the AHFE 2019 International Conference on Human Aspects of Advanced Manufacturing, and the AHFE International Conference on Advanced Production Management and Process Control, July 24-28, 2019, Washington D.C., USA /: proceedings of the AHFE 2019 International Conference on Human Aspects of Advanced Manufacturing, and the AHFE International Conference on Advanced Production Management and Process Control, July 24-28, 2019, Washington D.C., USA. ([2020]) - Unknown
No abstract available